Determinan BOPO Pada Perbankan Syariah Periode 2018.Q1-2023.Q2: Firm Size Sebagai Variabel Moderasi - Febrian, Neyzha Virela Lourencia; Budianto, Eka Wahyu Hestya (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze the influence of ZISWAF Fund Receipts, NPF Nett, and Musyarakah Income on BOPO in Islamic banks in Indonesia, by considering company size as a moderating variable. The research sample includes five sharia banks: Bank Muamalat Indonesia, Bank Syariah Indonesia, Bank Victoria Syariah, Bank Mega Syariah, and Bank Panin Dubai Syariah, in the period 2018.Q1-2023Q3. Data were analyzed using panel data analysis and MRA with the Eviews 12 application. The research results showed that ZISWAF Fund Receipts, NPF Nett, and Musyarakah Income did not have a significant effect on BOPO individually. However, simultaneously these three variables have a significant effect on BOPO. Company size does not moderate the influence of these variables on BOPO.